2018
DOI: 10.1108/ijqrm-06-2017-0117
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis-validated comprehensive employee job performance scale

Abstract: Purpose The purpose of this paper is to develop an employee job performance (EJP) scale questionnaire that encompasses the job time, job quality and job quantity dimensions of employee performance. Design/methodology/approach In this study, the questionnaire questions were first validated using exploratory factor analysis (EFA) and then confirmatory factor analysis (CFA) along the three performance dimensions. The research samples were auto-parts assembly line workers. The factor analysis results confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 39 publications
4
66
2
5
Order By: Relevance
“…All instruments were assessed using existing scales. Employee job performance was assessed following Na-Nan et al (2018a) as three dimensions of quality, quantity and time. Knowledge sharing was assessed following Kang et al (2008) as four questions in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All instruments were assessed using existing scales. Employee job performance was assessed following Na-Nan et al (2018a) as three dimensions of quality, quantity and time. Knowledge sharing was assessed following Kang et al (2008) as four questions in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Na-Nan et al (2018a) identify three dimensions of employee job performance as quality, quantity and time. The quality dimension considers the ability to perform tasks according to criteria or standards required by the workplace (Peterson and Plowman, 1953).…”
Section: Employee Job Performancementioning
confidence: 99%
“…Feasibility studies are often undertaken to refine protocols and procedures. Furthermore, Na-Nan et al (2018 ) suggested that the methodology of the bias reduction of social research should recognise that culture, economics, politics, technology and language can also influence questionnaire validation. Thus, variations occurring in other cross-cultural or context settings should also be investigated.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Employee performance of job evaluates whether an individual performs his or her job effectively. In this way, individual performance can be characterized into two i.e., performed a behavior as specified in the description of the job and the second one in response to environment, not directions (Na-Nan, Chaiprasit, & Pukkeeree, 2018). Besides, Choudhury (2011) stated that employee behavior and performance is influenced by the organizational environment in which they work.…”
Section: Review Of Literaturementioning
confidence: 99%